2020
DOI: 10.3389/fphys.2020.594116
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Glycosyltransferases and Albendazole Metabolism in the Juvenile Stages of Haemonchus contortus

Abstract: The nematode Haemonchus contortus, a gastrointestinal parasite of ruminants, can severely burden livestock production. Although anthelmintics are the mainstay in the treatment of haemonchosis, their efficacy diminishes due to drug-resistance development in H. contortus. An increased anthelmintics inactivation via biotransformation belongs to a significant drug-resistance mechanism in H. contortus. UDP-glycosyltransferases (UGTs) participate in the metabolic inactivation of anthelmintics and other xenobiotic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…As generally recommended for a transcriptional response study, two exposure times (4 h and 12 h) were used. Not many UGTs were upregulated by ABZ nor ABZSO after 4-h exposure both in the males and females, with more transcripts upregulated in males after 12 h. Similarly, the 4-h exposure to ABZ did not lead to any induction of UGTs in the juvenile stages ( Kellerova et al, 2020a ), a result also found with ABZ in very high concentrations in H. contortus adults ( Stasiuk et al, 2019 ). On the other hand, the exposure of H. contortus adults to sub-lethal concentrations of ABZ and ABZSO (1 μM and lower) for 4 and 12 h ex vivo ( Kellerova et al, 2020b ), and for several weeks in vivo ( Dimunová et al, 2022 ) led to the transcriptional response of several UGTs ( Table 4 ).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…As generally recommended for a transcriptional response study, two exposure times (4 h and 12 h) were used. Not many UGTs were upregulated by ABZ nor ABZSO after 4-h exposure both in the males and females, with more transcripts upregulated in males after 12 h. Similarly, the 4-h exposure to ABZ did not lead to any induction of UGTs in the juvenile stages ( Kellerova et al, 2020a ), a result also found with ABZ in very high concentrations in H. contortus adults ( Stasiuk et al, 2019 ). On the other hand, the exposure of H. contortus adults to sub-lethal concentrations of ABZ and ABZSO (1 μM and lower) for 4 and 12 h ex vivo ( Kellerova et al, 2020b ), and for several weeks in vivo ( Dimunová et al, 2022 ) led to the transcriptional response of several UGTs ( Table 4 ).…”
Section: Discussionmentioning
confidence: 61%
“…enhanced survival ( Fontaine and Choe, 2018 ). The transcription level of UGTs in H. contortus fluctuates during ontogenetic development, with most of the UGTs showing a higher expression in juvenile stages, possibly due to the greater levels of environmental toxins to which the free-living stages are exposed ( Kellerova et al, 2020a ). The connection between UGTs and anthelmintics resistance in H. contortus has been suggested due to the enhanced production of glycosides ( Stuchlikova et al, 2018 ) and higher constitutive expression of UGT368B2 in resistant than in sensitive strains ( Matouskova et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations